Strategi Guru Dalam Menumbuhkan Sikap Kemandirian Belajar Siswa Kelas 2A di SDN 76 Kota Bengkulu - Putri Surya Anita; Thiara Deah Lestari; Yolanda Deska Pratama; Melisa Putri Dwi Ningrum (Yayasan Darusssalam Bengkulu, 2024)
This research is field research with the aim of finding out the strategies and problems faced by teachers in fostering learning independence for class 2A students at SDN 76, Bengkulu city. The researcher used a research method with a qualitative descriptive approach with the research subjects namely the class teacher and class 2A students. Data collection techniques use observation and interview techniques. This interview technique was carried out to obtain information regarding the strategies and problems faced by teachers in fostering students' independent learning attitudes. The data analysis used by researchers went through three stages such as data reduction, data display and drawing conclusions. Based on the results of the data analysis that has been carried out, there has been an increase in learning independence for several students after implementing the contextual learning approach. By using this contextual approach, children's learning can become more meaningful, relevant, and can help children develop a deeper understanding of the world around them. Apart from implementing a contextual learning approach, the class 2A teacher at SDN 76 Bengkulu city also applies a strategy of giving responsibility, where the teacher gives responsibility to students to manage their own time, make study schedules, complete assignments independently, so that they do not depend on others. However, in cultivating an attitude of independent learning in students, there are several problems faced by class 2A teachers at SDN 76, Bengkulu City, for example, children are still dependent on other people and the environment around them.